Analisis Peran Sistem Pengendalian Manajemen terhadap Peningkatan Operasional Penjualan Kargo PT. Garuda Indonesia Semarang - Kholilul Kholik; Intan Nur Azizah; Dita Safira Harahap; Very Ikhsan Pane; Revan Syahputra; Jihan Rindi Antika; Tasya Fadila (Pusat Riset dan Inovasi Nasional, 2026)
This article aims to analyze the role of management control systems in improving cargo sales operations at PT Garuda Indonesia (Persero) Tbk Branch Office Semarang. The rapid growth of the air logistics industry requires airlines to enhance operational effectiveness, particularly in cargo sales, which represent a major source of company revenue. This article employs a qualitative approach using a literature review method. Data were collected from relevant and credible secondary sources, including scientific journals, academic books, previous research reports, and official company documents. Data analysis was conducted through content analysis and comparative analysis using thematic coding to identify key patterns and concepts related to management control systems and cargo sales operations. The findings indicate that management control systems play a crucial role in strengthening coordination among work units, improving performance monitoring mechanisms, and ensuring that cargo sales operations are aligned with established targets and procedures. Effective implementation of management control systems also contributes to increased operational productivity and supports the company’s competitiveness within the highly competitive air logistics industry.